Studies of Patients with Trauma-Related Hemorrhage: What Patient Outcomes are Examined and When? A Systematic Review - Miller JL; Patrician PA; Jones AR (Nursing: Research and Reviews)
Justin L Miller, Patricia A Patrician, Allison R Jones School of Nursing, The University of Alabama at Birmingham, Birmingham, AL, USACorrespondence: Justin L Miller, Email jlmiller@uab.eduAim: To determine outcomes measured following blood transfusion for the resuscitation of adult patients who experienced trauma-related hemorrhage and compare them based on the timeframe in which they occurred: short-, intermediate-, and long-term.Design: Systematic Review.Review methods: We included articles that met the following criteria: published in English between January 1, 2014 and December 31, 2023; with full text available; peer-reviewed; and adult population (≥ 19 years). Two authors reviewed each title, abstract, and full text for inclusion using the online review tool, Covidence; a third author adjudicated conflicts. A similar method was used for data extraction. Outcomes were categorized as those that occurred in the short-term (day of injury to < 30 days post-injury), intermediate-term (30 days to six months post-injury), and long-term (> six months to one year post-injury). The Grading of Recommendations Assessment, Development, and Evaluation (GRADE) system was used to rate the quality and strength of the reviewed evidence.Data Sources: PubMED, CINAHL, Scopus, and Embase.Results: The final analysis included 50 articles. Outcomes were categorized as those related to mortality, pathophysiologic outcomes, indices of coagulopathy, and duration of treatment. All four outcome categories were reported in at least one study during the short-term timeframe. Mortality was reported in 12 articles, the duration of treatment was reported in four articles, and pathophysiologic outcomes were reported in one article during the intermediate-term timeframe. Two articles reported mortality during the long-term timeframe.Conclusion: Short-term outcomes of patients resuscitated with blood products following a trauma-related hemorrhage have been well studied. Future studies are needed to assess the intermediate- and long-term outcomes of patients following a trauma-related hemorrhage.Impact: Understanding patient outcomes following trauma-related hemorrhage may help guide clinicians in the provision of care beyond the initial resuscitation period, and ultimately improve patient recovery and rehabilitation.Keywords: blood transfusion, wounds and injuries, trauma, hemorrhage, patient outcomes